Understanding the difference, makes the difference: perceptions of Black and Minoritised ethnic occupational therapists on mentoring - Anita Atwal; Elizabeth McKay; Vimal Sriram (BMC, 2023)
Abstract Introduction Black and Minoritised Ethnicity (BME) occupational therapists face lower career progression opportunities and mentoring is one possible intervention that may offer support. BME persons may have different expectations and experiences from their mentor, and research exploring their perceptions of mentoring is important. In Occupational Therapy there is a growing awareness of the need to be true to the values of social justice. The aim of this research is to learn about BME occupational therapists' experiences and perceptions of mentoring for career progression. Methods Four online focus groups involving 19 participants from the UK were held, discussions were facilitated by researchers using a topic guide. Participants responses were analysed, and codes were brought together to create Themes including career progression and role models, mentoring relationship, similarity with the mentor and outcomes from mentoring. Results The study highlighted that trust is integral to effective mentoring relationships and BME occupational therapists want mentors who they can trust with their experiences and stories. Compatibility between mentors and mentees in terms of personality, values, and working styles is crucial for effective mentoring relationships. Providing opportunities for networking, acknowledging good work and giving permission were all seen as outcomes from good mentoring. The absence of BME role models and ingroup bias were also reported as issues to be addressed. Conclusion This study explores the perception of mentorship as a mechanism for career advancement in occupational therapists from BME backgrounds, with these results transferable to other health and care professional groups. We recommend the creation of a mentoring charter for BME healthcare workers in the United Kingdom to ensure that those from BME backgrounds feel supported, mentored, and provided with equitable access to resources, including adequate mentoring and networking opportunities.